KEEPING AND FEEDING KARAKUL SHEEP ON PASTURES IN SURKHANDARYA REGION - U. Sh. Saydaliev; Sh.B. Kurbonov (TADQIQOTLAR, 2026)
Annotasion. The article describes the feeding standards for Karakul sheep, the annual  nutrient  requirements  of  Karakul  sheep,  the  pasture  diet  and  their  seasonal nutrition, feeding standards for Karakul sheep of different sexes and ages, as well as feeding standards for Karakul sheep supplementary feeding.